Analysis of Local Culture Actualization on Village Fund Management - Jeliastiva Jeliastiva (Journal of Social Commerce, 2022)
This research tries to evaluate the extent to which local culture impacts the financial management of villages. This research was done using a qualitative methodology. The author of this research collected data via observation, interviews, and documentation. These methods allow the author to have an intimate awareness of the field's circumstances. According to the findings of this research, the local administration has a comprehensive awareness of the cultural norms and values of the community. The incorporation of regional cultural norms into village financial management has a good effect. This is carried out to deter dishonesty, illegal activity, and greed. The administrative officials of the village are able to conduct themselves in a more fair and trustworthy manner while maintaining a tough and responsible posture. Since the principles of openness, accountability, and participatory management have been adopted, the administration of the fund has been very effective.